Study of the effect of silver in the mechanical properties and electrical conductivity of duralumins (al-4%cu-0.5%mg) (2014)
This study evaluated the effect of the silver content of Al-Cu based alloys on the microstructure, the tensile strength, the electrical resistance and the temperature increase with the passage of electric current (Joule effect). For that purpose, Al-4% Cu-0, 5% Mg alloys were tested with silver content in proportions of 1.5%, 2.5% and 3.5%. Precipitation hardening was carried out by homogenization heat treatment of solid solutions. The microstructure analysis was carried out using optical microscope and SEM, Vickers hardness tests was also performed, tests of tensile strength and electrical conductivity, which were compared with the alloy A356-T6. The results of this research show that the increase of silver in the alloy increased tensile strength and decreases the resistivity. By SEM and EDS analysis of the phase q (CuAl2), Al6 (Cu, Fe) and Al7Cu2Fe was observed.